2022
DOI: 10.1007/s00429-021-02450-1
|View full text |Cite|
|
Sign up to set email alerts
|

Ketogenic diet impairs neurological development of neonatal rats and affects biochemical composition of maternal brains: evidence of functional recovery in pups

Abstract: The ketogenic diet (KD) is a type of diet in which the intake of fats significantly increases at the cost of carbohydrates while maintaining an adequate amount of proteins. This kind of diet has been successfully used in clinical therapies of drug-resistant epilepsy, but there is still insufficient evidence on its safety when used in pregnancy. To assess KD effects on the course of gestation and fetal development, pregnant females were fed with: (i) KD during pregnancy and lactation periods (KD group), (ii) KD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
11
1
Order By: Relevance
“…It is also worth mentioning here, that at the beginning of postnatal life, the offspring of mothers fed with KD during pregnancy had significantly lower body mass what was described in details in our previous work . When, on the 2nd day postpartum, in KD-fed mothers, normal diet was introduced, and their progeny began to rebuilt the body mass very quickly.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…It is also worth mentioning here, that at the beginning of postnatal life, the offspring of mothers fed with KD during pregnancy had significantly lower body mass what was described in details in our previous work . When, on the 2nd day postpartum, in KD-fed mothers, normal diet was introduced, and their progeny began to rebuilt the body mass very quickly.…”
Section: Discussionsupporting
confidence: 54%
“…The immature brain is able to take up KB from two to three times more efficiently than the mature one and use them for energy metabolism and lipid as well amino acid biosynthesis. , Our earlier study carried out on adults male Wistar rats showed increased intensity of the band at 1740 cm –1 in hippocampal formation of animals fed with KD . On the other hand, we did not notice an elevated level of this band in the females fed with KD 2 days postpartum, although the level of β-hydroxybutyrate in their blood was significantly higher both on the day of fertilization as well as on 4th, 15th, and 20th gestational day …”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations